Pengaruh Word of Mouth, Variasi Produk, dan Persepsi Konsumen terhadap Keputusan Pembelian Produk Balket (Balung Kethek) di Dafinas Snack Boyolali - Fika Luxsmawati; Luki Sri Anggorowati; Listyowati Puji Rahayu (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the influence of Word of Mouth (WOM), product variety, and consumer perception on purchasing decisions for Balket (Balung Kethek) products at Dafinas Snack Boyolali. The study employs a quantitative approach, with data collected via questionnaires distributed to 100 respondents who had purchased Balket products. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) software, utilizing validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that Word of Mouth has a positive and significant effect on purchasing decisions, with a significance value of 0.010 (< 0.05). Meanwhile, product variety does not have a significant effect on purchasing decisions, as evidenced by a significance value of 0.288 (> 0.05). Conversely, consumer perception has a positive and significant effect on purchasing decisions, with a significance value of 0.000 (< 0.05). Simultaneously, Word of Mouth, product variety, and consumer perception significantly influence purchasing decisions. The adjusted R-square value of 0.403 indicates that the three independent variables explain 40.3% of the variation in purchasing decisions, while the remaining 59.7% is influenced by factors outside the research model.